Tanggapan Siswa Terhadap Penggunaan Video Pembelajaran Berbasis Youtube Hubungannya dengan Hasil Belajar Kognitif Mereka pada Mata Pelajaran PAI dan Budi Pekerti SMPN 3 Bandung - Cecep Anwar; Asep Andi Rahman; Azahra Auliana Fitri (Gunung Djati Conference Series, 2022)
The purpose of this study is to determine the relationship between student responses to the use of YouTube learning videos and the cognitive learning outcomes of PAI and Budi Pekerti. The method used is correlational with a quantitative approach. Respondents were 44 students of class VIII. The results of this study: 1) The reality of student responses to the use of youtube-based learning videos (X) is classified as good with an average final score of 3.72. 2) The reality of students' cognitive learning outcomes in PAI and Budi Pekerti (Y) subjects is classified as very good with an average score of 84.3. 3) The relationship between variables X and Y is positive and significant, indicated by rxy = 0.91, correlation significance test tcount 14.39 > ttable 2.02. The conclusion of the study is that there is a positive and significant correlation. The higher students' responses to the use of youtube-based learning videos, the higher their cognitive learning outcomes in PAI and Budi Pekerti subjects.